Maximize Long Drive: The Role of Arm Muscle Strength in Balinese Woodball Athletes - Puspitasari, Ni Putu Ayu Intan; Pramana, I Putu Yudi; Kamayoga, I Dewa Alit; Jawi, I Made (Majalah Ilmiah Fisioterapi Indonesia; Vol 12 No 3 (2024): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/mifi.2024.v12.i03.p12, 2024)
Introduction : Woodball is an outdoor sport played individually or in teams, where players hit a ball with a mallet to pass it through a gate using as few strokes as possible. Mastering the long drive shot is essential for success, as it helps cover long fairways in fewer strokes. This study examines the relationship between arm muscle strength and long drive distance in woodball athletes in Bali. Methods : Using a cross-sectional approach, this observational analytic study used purposive sampling to select 50 athletes aged 15-18 who participated in the 2023 Youth Pledge Cup. Data were collected using a hand dynamometer to measure arm muscle strength and a 30-meter course to measure long drive distances. Athletes took two shots, and distances were categorized into over 30 meters and under 30 meters. Results : Spearman-Rho analysis showed a p-value of 0.000 (p < 0.05) and an r-value of 0.569, indicating a statistically significant and direct correlation between increased arm muscle strength and long drive distance. The r-value suggests a moderate to strong correlation, emphasizing the importance of arm muscle strength in enhancing long-drive performance. Conclusion : There is a strong correlation between arm muscle strength and long-drive performance in woodball athletes in Bali.   Keywords : arm muscle strength, long drive shot, woodball athletes